ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8683792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-intrusive Load Monitoring Algorithms for Appliance-level Anomaly Detection

Abstract: Appliance fault in buildings resulting in abnormal energy consumption is known as an anomaly. Traditionally, anomaly detection is performed either at aggregate, i.e., meter-level, or at appliance level. Meter-level anomaly detection does not identify the anomaly-causing appliance, while appliance-level detection requires submetering each appliance in the building. Non-Intrusive Load Monitoring (NILM) has been proposed as an alternative to submetering to detect when appliances are running as well as estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Rashid et al [69] identified and defined factor models to reduce dimension. Furthermore, the author presented a new approach to estimate high-dimensional factor models, using the empirical spectral density of residuals.…”
Section: Mathematical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rashid et al [69] identified and defined factor models to reduce dimension. Furthermore, the author presented a new approach to estimate high-dimensional factor models, using the empirical spectral density of residuals.…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…Rashid et al [69] proposed a revised method based on the non-intrusive load monitoring theory. They constructed a workload model by using the REFIT dataset from smart-meter devices and regarded it as a built-in prediction model for the method.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…Although, these systems have been thoroughly probed from both intrusive and non-intrusive aspects, their anomaly detection capability has not been fairly taken into consideration. In terms of Non-Intrusive Load Monitoring (NILM), few studies have only investigated the proficiency of load disaggregation methods for anomaly detection [12], [13]. Furthermore, in [11], we have aimed to design a NILM system for diagnosis purposes.…”
Section: B Motivation and Contributionmentioning
confidence: 99%
“…Besides, other studies have mainly examined the proficiency of NILM methods for anomaly detection. Rashid et al have evaluated the ability of household appliances load disaggregation techniques for anomaly detection [13]. Likewise, they have concluded that enhanced NILM algorithms are required to achieve such an ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation